COMPARISON ADDED VALUE OF PALM SUGAR AND GRANULATED PALM SUGAR AT MUTIARA FARMER GROUP IN LAREH SAGO HALABAN DISTRICT - Filiani, Wimby; Yelfiarita, Yelfiarita; Veronice, Veronice (Jurnal Sains Agribisnis, 2021)
The main derivative product of sugar palm is Nira. Carrying out activities to process palm sap into palm sugar and palm sugar will increase the added value of the palm Nira. This study aims to1) analyze the production process of palm sugar and granulated palm sugar. 2)To compare the added value produced by members of the Mutiara Farmer Group in Lareh Sago Halaban District in processing them. The analysis used is quantitative and qualitative analysis. This research was conducted using primary data and secondary data. Primary data obtained from observation, documentation, interviews and secondary data obtained from relevant sources, scientific literature, related institutions or agencies and literature studies. Based on the research that has been done, it can be concluded that 1) The processing activities of palm sugar and granulated palm sugar are not much different, both with the concept of cooking with high heat and a long time, but in the activities there are differences where palm sugar is printed while granulated palm sugar is milled and sifting. 2) The ratio of added value of palm sugar is 59,95% and the ratio of added value of granulated sugar is 71,19%. These two products are in the "high" category because they are > 40%. 3) And the comparison of the added value of granulated palm sugar business is 24,56% higher than palm sugar business. Keywords: Added Value; Granulated Palm Sugar; Sugar Palm